Hydrophobic cell surface display system of PETase as a sustainable biocatalyst for PET degradation - Jia, Yunpu; Samak, Nadia A.; Hao, Xuemi; Chen, Zheng; Wen, Qifeng; Xing, Jianmin (Frontiers in Microbiology, 2022)
PETase from Ideonella sakaiensis 201-F6 exhibits a great potential in polyethylene terephthalate (PET) waste management due to it can efficiently degrade PET at moderate conditions. However, its low yield and poor accessibility to bulky substrates hamper its further industrial application. Herein a multigene fusion strategy is introduced for the construction of hydrophobic cell surface display (HCSD) system in E. coli as a robust, recyclable, and sustainable whole-cell catalyst. The truncated outer membrane hybrid protein FadL exposed the PETase and hydrophobic protein HFBII on the surface of E. coli with efficient PET accessibility and degradation performance. E. coli containing the HCSD system changed the surface tension of the bacterial solution, resulting in a smaller contact angle (83.9 ± 2° vs. 58.5 ± 1°) of the system on the PET surface, thus giving a better opportunity for PETase to interact with PET. Furthermore, pretreatment of PET with HCSD showed rougher surfaces with greater hydrophilicity (contact angle of 68.4 ± 1° vs. 86.1 ± 2°) than the non-pretreated ones. Moreover, the HCSD system showed excellent sustainable degradation performance for PET bottles with a higher degradation rate than free PETase. The HCSD degradation system also had excellent stability, maintaining 73% of its initial activity after seven days of incubation at 40 ℃ and retaining 70 % activity after seven cycles. This study indicates that the HCSD system could be used as a novel catalyst for efficiently accelerating PET biodegradation.